(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
With Brazil’s accession to the Additional Protocol to the United Nations Convention against Transnational Organized Crime on the Prevention, Suppression and Punishment of Trafficking in Persons, Especially Women and Children, incorporated into the country’s legal system by Decree No. 5.017/2004, the Brazilian state recognized the need to stimulate the solidification of measures to combat this spurious activity in the repressive and preventive axes, as well as social monitoring and the development of assistance to victims. Thus, national plans to combat trafficking in human beings were drawn up; for a period, efforts were made to strengthen the regionalization of support networks for victims; discussions intensified on the best format for integrating the three axes of the fight against the problem. In short, the powers of the Republic, civil society and law enforcement agencies moved to try, in a more or less integrated and intersectoral way, to align themselves in the search to implement more appropriate measures to minimize the phenomenon. One of the measures adopted was the attempt to bring the repressive-criminal concept of trafficking in human beings closer to that established by the Additional Protocol to the Palermo Convention. With this text, we will try to present an appropriate exegetical solution, on the repressive side, to tackle trafficking in human beings, especially in cases where the individual’s expression of will is influenced by factors that trigger migration and, to some extent, their inclusion as a victim in a trafficking network, such as the feminization of poverty; the existence, in the host country, of a real demand which, in many cases, is not met by local citizens, especially in sectors in which the activity is stigmatized and degrading; the perception, sometimes unrealistic, of opportunities to improve one’s life by entering the destination nation.